2x(x+3)-7=4x-6

Simple and best practice solution for 2x(x+3)-7=4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+3)-7=4x-6 equation:


Simplifying
2x(x + 3) + -7 = 4x + -6

Reorder the terms:
2x(3 + x) + -7 = 4x + -6
(3 * 2x + x * 2x) + -7 = 4x + -6
(6x + 2x2) + -7 = 4x + -6

Reorder the terms:
-7 + 6x + 2x2 = 4x + -6

Reorder the terms:
-7 + 6x + 2x2 = -6 + 4x

Solving
-7 + 6x + 2x2 = -6 + 4x

Solving for variable 'x'.

Reorder the terms:
-7 + 6 + 6x + -4x + 2x2 = -6 + 4x + 6 + -4x

Combine like terms: -7 + 6 = -1
-1 + 6x + -4x + 2x2 = -6 + 4x + 6 + -4x

Combine like terms: 6x + -4x = 2x
-1 + 2x + 2x2 = -6 + 4x + 6 + -4x

Reorder the terms:
-1 + 2x + 2x2 = -6 + 6 + 4x + -4x

Combine like terms: -6 + 6 = 0
-1 + 2x + 2x2 = 0 + 4x + -4x
-1 + 2x + 2x2 = 4x + -4x

Combine like terms: 4x + -4x = 0
-1 + 2x + 2x2 = 0

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
-0.5 + x + x2 = 0

Move the constant term to the right:

Add '0.5' to each side of the equation.
-0.5 + x + 0.5 + x2 = 0 + 0.5

Reorder the terms:
-0.5 + 0.5 + x + x2 = 0 + 0.5

Combine like terms: -0.5 + 0.5 = 0.0
0.0 + x + x2 = 0 + 0.5
x + x2 = 0 + 0.5

Combine like terms: 0 + 0.5 = 0.5
x + x2 = 0.5

The x term is x.  Take half its coefficient (0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
 + 0.25 + x2 = 0.5 + 0.25

Combine like terms:  + 0.25 = 1.25
1.25 + x2 = 0.5 + 0.25

Combine like terms: 0.5 + 0.25 = 0.75
1.25 + x2 = 0.75

Factor a perfect square on the left side:
(x + 0.5)(x + 0.5) = 0.75

Calculate the square root of the right side: 0.866025404

Break this problem into two subproblems by setting 
(x + 0.5) equal to 0.866025404 and -0.866025404.

Subproblem 1

x + 0.5 = 0.866025404 Simplifying x + 0.5 = 0.866025404 Reorder the terms: 0.5 + x = 0.866025404 Solving 0.5 + x = 0.866025404 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 0.866025404 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 0.866025404 + -0.5 x = 0.866025404 + -0.5 Combine like terms: 0.866025404 + -0.5 = 0.366025404 x = 0.366025404 Simplifying x = 0.366025404

Subproblem 2

x + 0.5 = -0.866025404 Simplifying x + 0.5 = -0.866025404 Reorder the terms: 0.5 + x = -0.866025404 Solving 0.5 + x = -0.866025404 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -0.866025404 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -0.866025404 + -0.5 x = -0.866025404 + -0.5 Combine like terms: -0.866025404 + -0.5 = -1.366025404 x = -1.366025404 Simplifying x = -1.366025404

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.366025404, -1.366025404}

See similar equations:

| Y=9y-72 | | 2(4x-1)+3(3-2x)= | | n+3=5n | | -132.6x(-53.78)= | | (2+c)=5(2+c)-6(2+c) | | -2(y)+2.82(-5)=24 | | 4a+3-a=7+2+a | | (2x+1)=(4x-3) | | 4(x-1)=6x | | y=-1000x^2+1100x-2.5 | | 4(6-6)=8 | | 4(x-4)=6x | | 3(-1-2)+6(2-4)= | | 9x-6=102 | | 5(x-2)=3(x-3) | | 5(y-4)/3=2y-5 | | 2(x+9)=24 | | 2.22m=4.4 | | -17=0.20n-20 | | -5(b+3)=-7b-1 | | x+25=-3(x-7) | | Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 | | 9a=25b | | 8x-11=13x+15 |

Equations solver categories